323. Childhood Outcomes Following Parechovirus Central Nervous System Infection in Young Infants at a US Children's Hospital. (26th November 2018) - Selvarangan, Rangaraj; Kilbride, Howard; Jackson, Mary Anne
Abstract: Background: Parechovirus (PeV), specifically Parechovirus A type 3 (PeV-A3), is a picornavirus associated with severe infection in young infants, with disease manifestations ranging from undifferentiated fever, to sepsis like illness, and meningoencephalitis. There are limited data regarding long-term outcomes of infected infants. The objective of this study was to describe early childhood outcomes following infantile PeV-CNS infection Methods: Families of Infants hospitalized during 2014 with laboratory confirmed PeV-CNS infection were contacted for neurodevelopmental follow-up. Testing included medical history, standard neurologic examination, parental completion of Ages and Stages questionnaire (ASQ) and determination of Bayley III cognitive, motor, and language quotients. Neurodevelopmental impairment (NDI) was considered present if cognitive, motor, or language quotients were >1 standard deviation (mild) or >2 SD (severe) below the testing norms, the presence of cerebral palsy (CP), or sensory (vision/hearing) impairment. Relationship of childrens' outcomes to severity of PeV disease (uncomplicated febrile illness [mild], disseminated disease [moderate] or advanced disease requiring intensive care [severe]) was assessed by chi-square analysis. Results: Nineteen children were available for testing at approximately 3 years of age (31–38 months), 12 (63%) with mild, five (26%) moderate, and two (11%) with severe disease. Mean Bayley quotients were within normal limits (see table), one infant had mild CP (5%) and two (11%) had mild NDI. There was no apparent relationship of NDI with infant PeV clinical presentation. ASQ results included 11% at referral level and 32% suspect, and were unrelated to severity of the viral illness. However, all parents of children with moderate or severe presentations of infantile PeV disease had medical or behavior concerns at 3 years of age compared with 25% of those with mild presentation ( P = 0.007). Conclusion: Neurodevelopmental impairments may be seen following infant PeV disease, but may not correlate with severity of clinical disease. Longitudinal monitoring of developmental status through early childhood following PeV infantile disease is warranted. Disclosures: All authors: No reported disclosures.